Features of administrative proceedings in the Republic of Kazakhstan - Saniyazova, E.K.; Isayeva, Zh.A. (Bulletin of the Karaganda University “Law Series”, 2021)
The purpose of the article is to analyze the new Administrative Procedural Code of the Republic of Kazakhstan, which will enter into effect on July 1, 2021. The relevance of the problem is due to the fact that with the adoption and introduction of the new APPC in Kazakhstan the institute of administrative justice is being created, the purpose of which is to create a system of constitutional checks and balances. The newly created specialized administrative court will ensure the interests of the public in the sphere of the legality of the activities of the executive authorities. Analyzing the norms of the new APPC of the Republic of Kazakhstan, the authors rightly believe that the adoption of the APPC will lead to increased transparency and efficiency of the activities of state bodies, will become an effective mechanism for protecting the rights of citizens when considering public law disputes, as well as a guarantee that allows our citizens to take part in the decision-making process of the authorities.